Release or throw? Adopting good fishing practices can reduce post-release mortality of a critically endangered shark in artisanal fisheries in southern Brazil: Release or throw? Adopting good fishing practices can reduce post-release mortality of a critically endangered shark in artisanal fisheries in southern Brazil - dos Santos, Paulo Roberto Santos; Klafke, Kaliandra (Arquivos de Ciências do Mar, 2023)
In this study we report information on post-release mortality in artisanal fisheries of the Angular Angelshark Squatina guggenheim Marini, 1936, a critically endangered shark in Southeastern-South Brazil. We analyze artisanal fishing operations, which take place on the beachfront and verified that despite the release of all 74 captured sharks, about 30% were found stranded, debilitated or dead, a few minutes later, due to the release method (throwing). We suggest adjustments based on successful field integration experiences with fishers. Keywords: conservation, fishing, participative management, Squatina guggenheim